2006
DOI: 10.1088/0953-4075/39/8/001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the incoherent pumping field on the phase control of group velocity

Abstract: This paper studies the effects of the incoherent pumping field and the spontaneously generated coherence (SGC) on the phase control of group velocity. The effects of a relative phase between probe and coupling fields on the absorption and the dispersion are then discussed. It is shown that the phase dependence of the group velocity not only depends on the existence of the SGC, but also depends on the existence of the incoherent pump field. We show that for the weak probe field, and in the presence of SGC, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…A weak coupling field with frequency ω 41 and Rabi frequency g 41 is applied to transition |1 ↔ |4 . The weak probe field with frequency ω 23 and Rabi frequency g 23 = g p couples to transition |2 ↔ |3 . Finally, an incoherent driving field with pump strength Λ is applied to the probe transition.…”
Section: The Model Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A weak coupling field with frequency ω 41 and Rabi frequency g 41 is applied to transition |1 ↔ |4 . The weak probe field with frequency ω 23 and Rabi frequency g 23 = g p couples to transition |2 ↔ |3 . Finally, an incoherent driving field with pump strength Λ is applied to the probe transition.…”
Section: The Model Systemmentioning
confidence: 99%
“…Sub-and superluminal light propagation together with nonlinear optical gain or losses were observed in [22]. Two of the present authors suggested to use an incoherent pump field to control light propagation from subluminal to superluminal [23,24]. Recently, we have studied the light propagation of a probe pulse in a four-level double lambda system, where the applied laser fields form a closed interaction loop [25].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum interference arising from incoherent Page 3 of 20 A c c e p t e d M a n u s c r i p t pumping processes has been used for modifying spontaneous emission [31,32], phase dependence of collection fluorescence [33], and coherent population trapping [34]. The effect of incoherent pump field on phase control of group velocity and dynamical behavior of the absorption and dispersion has also been studied [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the combine effect of SGC and quantum interference of incoherent pump field make the system phase dependent; thus the optical properties of the medium such as amplification without population inversion, dispersion, absorption, and group velocity of a weak probe field can be controlled by the relative phase of applied fields [35,38]. In addition, quantum interference of incoherent pump field can dramatically modify the nonlinear response of the medium; thus optical bistability and multi-stability can be controlled by the quantum interference of incoherent pump field and spontaneous emission [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the incoherent pumping field as well as spontaneously generated coherence (SGC) [14] on controlling the group velocity of probe field has been discussed [15,16].…”
mentioning
confidence: 99%